Targeted therapy for pediatric central nervous system tumors harboring mutagenic tropomyosin receptor kinases - Cipri, Selene; Fabozzi, Francesco; Del Baldo, Giada; Milano, Giuseppe Maria; Boccuto, Luigi; Carai, Andrea; Mastronuzzi, Angela (Frontiers in Oncology, 2023)
The family of the neurotrophic tyrosine kinase receptor (NTRK) gene encodes for members of the tropomyosin receptor kinase (TRK) family. Rearrangements involving NTRK1/2/3 are rare oncogenic factors reported with variable frequencies in an extensive range of cancers in pediatrics and adult populations, although they are more common in the former than in the latter. The alterations in these genes are causative of the constitutive activation of TRKs that drive carcinogenesis. In 2017, first-generation TRK inhibitor (TRKi) larotrectinib was granted accelerated approval from the FDA, having demonstrated histologic-agnostic activity against NTRKs fusions tumors. Since this new era has begun, resistance to first-generation TRKi has been described and has opened the development of second-generation molecules, such as selitrectinib and repotrectinib. In this review, we provide a brief overview of the studies on NTRK alterations found in pediatric central nervous system tumors and first and second-generation TRKi useful in clinical practice.